Petroleum coke residue-containing aerated block and preparation method thereof

By modifying petroleum coke residue with biomineralized block copolymers and supramolecular interface integrators, the problems of low utilization rate and poor interfacial bonding of petroleum coke residue in aerated concrete have been solved, resulting in aerated block products with high strength, low density, and excellent thermal insulation, which promotes the resource utilization of industrial solid waste and the upgrading of the building materials industry.

CN121225971APending Publication Date: 2025-12-30BEIJING XIANGYUDA NEW BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511318036.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-16
Publication Date
2025-12-30

AI Technical Summary

Technical Problem

The low utilization rate and poor interfacial bonding of petroleum coke residue in aerated concrete result in insufficient strength of the finished product, making it difficult to meet the requirements of high-performance building materials.

Method used

Petroleum coke residue was modified using biomineralized block copolymers and supramolecular interface integrators. Through molecular design, directional adsorption and mineralization induction were formed on the surface of the coke residue, enhancing its interfacial bonding with the cement matrix and achieving cross-scale bridging by utilizing multiple interaction sites.

Benefits of technology

It significantly improves the compressive strength and volume stability of aerated concrete blocks, enhances thermal insulation performance, reduces raw material costs, aligns with the concept of green development, and has the potential for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005597647110000091
    Figure BDA0005597647110000091
Patent Text Reader

Abstract

The invention discloses an aerated block containing petroleum coke residues and a preparation method thereof in the field of resource utilization of building materials and solid wastes, the aerated block comprises the following raw materials: petroleum coke residues, ordinary Portland cement, quick lime, aluminum powder paste, dihydrate gypsum, a biomineralization block copolymer and a supramolecular interface integrating agent, and the raw materials are proportioned according to specific parts by weight. Wherein the biomineralized block copolymer is prepared by reacting monomethoxy polyethylene glycol with lactide under the action of a catalyst to generate a block copolymer, reacting the block copolymer with ethylenediamine, dialyzing and freeze-drying; the supramolecular interface integrating agent is prepared by the following steps: reacting isocyanate with hydroxypyridine to generate a methacrylate monomer containing a pyridine group, reacting the methacrylate monomer with a silane compound in a mixed solvent, and drying to obtain the supramolecular interface integrating agent. The comprehensive performance of the aerated block is improved through raw material optimization and process control.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of building materials and solid waste resource utilization, and particularly relates to an aerated block containing petroleum coke residue and a preparation method thereof. BACKGROUND

[0002] As a core component of building engineering, the performance of building wall materials directly affects the safety, durability and energy efficiency of buildings. Traditional wall materials are mainly clay bricks, but the production of clay bricks consumes a large amount of arable land resources, and the burning process has high energy consumption and large pollutant emissions, which seriously conflicts with the concept of sustainable development. In recent years, aerated concrete blocks have gradually become the mainstream wall material to replace clay bricks due to their light weight, high strength, good thermal insulation and good seismic performance. However, traditional aerated concrete is mainly made of cement, lime, sand or fly ash as the main raw material, and its performance is significantly affected by the quality fluctuations of raw materials. In addition, the uneven regional distribution of sand, fly ash and other resources and the environmental pressure caused by long-term mining restrict the further development of the aerated concrete industry. Under this background, developing new high-performance aerated concrete, especially using industrial solid waste to replace part of the traditional raw materials, has become an important direction for the transformation and upgrading of the industry.

[0003] High-value utilization of industrial solid waste is one of the key paths to solve resource shortage and environmental problems. Petroleum coke residue is a solid waste generated in the delayed coking device during petroleum refining, and its annual production is huge. Its main components are high-carbon residues and a small amount of inorganic minerals. At present, it is mostly treated by stacking or simple landfill, which not only occupies a large amount of land resources, but also may cause soil heavy metal pollution and groundwater deterioration due to rainwater leaching. Although some studies have attempted to use petroleum coke residue in cement-based materials and road bases, due to its strong surface inertness, low active component content, and unreasonable particle size distribution, direct use requires a large amount of water and a high amount of cementitious materials, and may lead to poor product volume stability, slow strength development, and other problems, which makes it difficult to meet the requirements of high-performance building materials. Especially in the field of aerated concrete, the introduction of petroleum coke residue can reduce raw material costs, but its compatibility with cement, lime and other cementitious systems is insufficient, the bubble structure is easily damaged, and the final product often has defects such as collapse, insufficient strength, etc., which limits its large-scale application in aerated concrete.

[0004] To address the aforementioned issues, existing research primarily focuses on improving the activity and compatibility of petroleum coke residue with cementitious systems through physical grinding, chemical activation, or the addition of polymer admixtures. However, physical grinding only refines particles and cannot fundamentally alter its chemical activity; while chemical activators can activate some active components, excessive use can increase the risk of alkali-aggregate reaction and is difficult to synergistically regulate the interfacial behavior of multiphase systems; traditional polymer admixtures, although improving slurry flowability or enhancing interfacial bonding, suffer from poor compatibility with the surface properties of petroleum coke residue and limited functionality, making it difficult to simultaneously improve the mechanical properties, volume stability, and durability of aerated concrete. Furthermore, in the aerated concrete preparation process, the gas generation of aluminum powder, slurry expansion, and setting and hardening require precise coordination. Traditional processes rely on experience for temperature and time control, making product quality unstable due to fluctuations in external conditions. Therefore, developing a high-performance aerated concrete based on petroleum coke residue, addressing its low activity, weak interfacial bonding, and large performance fluctuations through novel functional material design and process optimization, is of great significance for promoting the resource utilization of industrial solid waste and upgrading the technology of the aerated concrete industry. Summary of the Invention

[0005] The purpose of this invention is to provide an aerated concrete block containing petroleum coke residue and its preparation method, which solves the technical problems of low utilization rate of petroleum coke residue in aerated concrete blocks and poor interfacial bonding leading to insufficient product strength.

[0006] The present invention achieves the above objectives through the following technical solutions:

[0007] An aerated concrete block containing petroleum coke residue comprises the following raw materials in parts by weight:

[0008] Petroleum coke residue: 600-750 parts by weight;

[0009] Ordinary Portland cement: 120-200 parts by weight;

[0010] Quicklime: 80-120 parts by weight;

[0011] Aluminum powder paste: 0.6-1.2 parts by weight;

[0012] Dihydrate gypsum: 20-50 parts by weight;

[0013] Biomineralized block copolymer: 4-12 parts by weight;

[0014] Supramolecular interface integrator: 8-20 parts by weight;

[0015] The preparation method of the biomineralized block copolymer includes: A1, reacting monomethoxy polyethylene glycol and lactide under vacuum conditions at 110-112℃ with stannous octoate as a catalyst to obtain mPEG-b-PLA block copolymer, which is purified by methanol precipitation and then vacuum dried; A2, subsequently reacting mPEG-b-PLA with ethylenediamine in dimethyl sulfoxide solution at 40-42℃; and finally dialyzing and freeze-drying the product.

[0016] In this invention, a biomineralization block copolymer achieves its functions of dispersing, coating, and inducing mineralization of petroleum coke particles through precise molecular design. The copolymer is prepared by first performing ring-opening polymerization of monomethoxy polyethylene glycol and lactide in a high-temperature vacuum environment under the action of a catalyst, forming an amphiphilic block copolymer. The polyethylene glycol segments provide hydrophilicity and steric hindrance, while the lactide segments impart hydrophobic properties. Subsequently, active amine groups are introduced through the aminolysis reaction of ethylenediamine, enabling the copolymer ends to coordinate with inorganic ions. This structural characteristic allows for directional adsorption on the surface of petroleum coke: hydrophobic segments anchor to the organic components of the coke, while hydrophilic segments extend into the aqueous phase, effectively preventing particle agglomeration. More importantly, the amine groups can form coordination bonds with calcium ions in cement hydration products, inducing directional crystallization of hydrated calcium silicate at its interface, thereby strengthening the interfacial bonding between petroleum coke and the cement matrix. This process simulates the molecular template effect in biomineralization, regulating the nucleation and growth of inorganic minerals through organic molecules, ultimately forming a dense mineralized layer on the surface of petroleum coke residue, which significantly improves its compatibility and mechanical contribution in cement matrix.

[0017] According to a preferred embodiment of the present invention, in step A1, the reaction time under vacuum conditions at 110-112°C is 24-30 h.

[0018] According to a preferred embodiment of the present invention, in step A2, the reaction time in the dimethyl sulfoxide solution at 40-42°C is 48-50 h.

[0019] According to a preferred embodiment of the present invention, the preparation method of the supramolecular interface integrator includes: B1, adding 2-(methacryloyloxy)ethyl isocyanate and 4-hydroxypyridine to anhydrous tetrahydrofuran and reacting at 60-65°C under the catalysis of dibutyltin dilaurate to obtain a methacrylate monomer containing a pyridine group; B2, dissolving the methacrylate monomer containing a pyridine group and 3-(methacryloyloxy)propyltriethoxysilane in a mixed solvent of ethanol and water, adding 2,2'-azobis(2-methylpropylimidazolium) hydrochloride, and reacting at 70-74°C under nitrogen protection, followed by vacuum drying after the reaction is completed.

[0020] In this invention, a supramolecular interface integrator achieves cross-scale bridging between petroleum coke residue and cement hydration products through multiple interaction sites in its molecular structure. Its synthesis consists of two key stages: First, an addition reaction between isocyanate and hydroxypyridine generates a functional monomer containing both a pyridine ring and an acrylate double bond. The pyridine ring possesses significant electron-donating and accepting properties, enabling strong adsorption to the polycyclic aromatic hydrocarbon structure of petroleum coke residue through π-π stacking interactions, while its nitrogen atom can form coordinate bonds with metal ions. In the second stage, this monomer is copolymerized with a silane-containing acrylate monomer to form a polymer possessing both supramolecular recognition capabilities and silanol hydrolysis activity. During mixing, the silane end groups hydrolyze to generate silanol, which condenses with the hydroxyl groups on the surface of the petroleum coke residue to form covalent bonds, while the pyridine ring is tightly adsorbed onto the coke residue surface through van der Waals forces and charge transfer interactions. Furthermore, the silanol can also condense with the silanols in the cement hydration products, forming siloxane bridges at the interface. This amphiphilic design enables the integrator to build a strong chemical bridge between petroleum coke and the cement matrix. At the same time, its supramolecular structure can alleviate stress concentration through dynamic reversibility, significantly enhancing the toughness and durability of the interface.

[0021] According to a preferred embodiment of the present invention, in step B1, the reaction time at 60-65°C is 12-14 hours.

[0022] According to a preferred embodiment of the present invention, in step B2, the reaction time at 70-74°C is 12-14 hours.

[0023] The present invention also provides a method for preparing the aforementioned aerated concrete block containing petroleum coke residue, the steps of which include:

[0024] S1. Petroleum coke residue is coarsely crushed by a jaw crusher and then ground in a ball mill; the petroleum coke residue powder is then dry-mixed with a supramolecular interface integrator and a biomineralized block copolymer in a high-speed shear mixer;

[0025] S2. Premix ordinary silicate cement, quicklime, and dihydrate gypsum in a forced mixing pot; then dry mix modified petroleum coke residue in the mixing pot; add water and mix at high speed to form a uniform slurry; after dispersing aluminum powder paste with water at 38-42℃ and soap pod powder foam stabilizer, add it to the slurry, mix at high speed, and immediately pour it into the mold; let it stand in a curing chamber at 53-57℃ to generate gas and pre-cur, then demold and mechanically cut.

[0026] S3. Finally, the billet is sent into the autoclave, heated to 182-184℃, and cured under constant pressure at 1.0-1.2MPa saturated steam pressure. Then the pressure and temperature are reduced, and the billet is allowed to cool naturally after being taken out of the autoclave.

[0027] In this invention, the preparation process of aerated concrete blocks is essentially a complex physicochemical process involving the synergistic effects of various cementing materials, lightweight aggregates, and functional additives in a multiphase system. Petroleum coke residue is first crushed and ground to obtain a specific particle size distribution, and then rapidly dry-mixed with a biomineralized block copolymer and a supramolecular interface integrator. During this process, the two polymers coat the surface of the coke residue through molecular chain entanglement and adsorption, and functional group coordination, respectively, achieving organic modification and significantly improving its compatibility with the inorganic cementing system. When the modified coke residue is mixed with cement, lime, gypsum, and other cementing materials, the system enters the hydration reaction-dominated stage: quicklime rapidly hydrates, releasing a large amount of heat and providing an alkaline environment, prompting aluminum powder paste to react with the alkali to produce hydrogen gas, forming a uniform closed-cell structure; dihydrate gypsum regulates the cement hydration rate, promoting the formation of ettringite to stabilize early strength; calcium ions generated during cement hydration coordinate with the copolymer amine groups, inducing the directional growth of hydration products on the coke residue surface. During the autoclaving stage, a high-temperature, high-pressure saturated steam environment triggers a deep hydrothermal reaction. The siliceous components dissolve in an alkaline medium and combine with calcium ions to form highly crystalline tobermorite crystals. These crystals interweave to form a network structure, endowing the product with high strength. Simultaneously, the silane end groups of the supramolecular interface integrator undergo a condensation reaction with the silanol groups on the tobermorite surface, forming a covalently bonded interface. Meanwhile, the biomineralization copolymer regulates crystal orientation growth, enabling the hydration products and petroleum coke residue to achieve molecular-level bonding. Ultimately, a composite structure is formed with petroleum coke residue as the core and hydration products as the shell. The supramolecular interface integrator constructs a flexible buffer layer between organic and inorganic phases, while the biomineralization copolymer achieves biomimetic mineralization reinforcement of the interface region. Together, they ensure that the aerated concrete block retains excellent mechanical properties and durability while maintaining its lightweight nature.

[0028] According to a preferred embodiment of the present invention, in step S1, the dry mixing speed is 2000-2200 rpm and the dry mixing time is 15-20 min.

[0029] According to a preferred embodiment of the present invention, in step S2, the premixing time is 2-4 min; the dry mixing time is 3-5 min.

[0030] According to a preferred embodiment of the present invention, in step S3, the constant pressure curing time is 12-14 hours.

[0031] The beneficial effects of this invention are as follows:

[0032] The petroleum coke residue aerated blocks and their preparation method provided by this invention achieve multiple significant technical effects through unique material design and process innovation, providing a brand-new technical path for solving the high-value-added resource utilization of petroleum coke residue. Its comprehensive advantages are reflected in the following aspects.

[0033] First, this invention fundamentally overcomes the long-standing technical bottleneck of using petroleum coke slag as a siliceous material in the building materials field. Due to its extremely high carbon content, petroleum coke slag exhibits stubborn chemical inertness and hydrophobicity, resulting in extremely poor compatibility with traditional cementitious matrices. Direct use leads to porous structures and low strength in finished products. This invention uniquely employs two functionally complementary modified compounds to achieve deep activation and efficient bridging of the petroleum coke slag surface at the molecular level. The biomineralized block copolymer, through its special structural design, can be directionally adsorbed onto carbonaceous surfaces and effectively induce heterogeneous nucleation and growth of cement hydration products at its interface in a hydration environment. This transforms the originally inert filler particles into active components actively participating in the hydration reaction, greatly enhancing interfacial bonding strength. Supramolecular interface integrators utilize their sophisticated molecular structure. One end is firmly anchored to the carbon layer surface of petroleum coke residue through strong supramolecular forces, while the other end forms a strong covalent bond with cement hydration products through hydrolyzable silane groups. This is like building countless strong "molecular bridges" between two materials with very different properties, thus completely solving the core problem of weak interfaces.

[0034] Secondly, the aforementioned synergistic modification mechanism leads to a leap in product performance. The aerated concrete blocks prepared using this invention exhibit fundamentally improved macroscopic mechanical properties, with a significantly increased compressive strength compared to unmodified products, fully meeting or even exceeding the requirements for superior-grade products in relevant national standards. Simultaneously, due to the strengthening and optimization of the interface structure, the volume stability of the product is significantly enhanced, and the drying shrinkage value is effectively controlled at an extremely low level, greatly reducing the risk of wall cracking and ensuring durability. Its internal pore structure is more uniform and delicate due to improved slurry fluidity and compatibility, further endowing the product with excellent thermal insulation and sound insulation properties. The entire preparation process is smooth and stable, the modification process requires no harsh conditions, it has high compatibility with existing autoclaved aerated concrete production lines, and the modifier dosage is small but the effect is significant, possessing enormous potential for large-scale production.

[0035] Finally, the successful implementation of this invention has generated significant economic and environmental benefits. It successfully transforms bulk industrial solid waste, petroleum coke residue, into a high-value main raw material for building materials, significantly reducing raw material costs. This technology not only alleviates the burden of solid waste disposal and environmental risks for the petroleum refining industry, aligning with the green development concept of a circular economy, but also opens up a stable and reliable new source of raw materials for the building materials industry, reducing dependence on traditional siliceous materials such as fly ash. It has broad market application prospects and positive social significance. In summary, this invention is an advanced technology that combines innovation, practicality, and environmental friendliness. Detailed Implementation

[0036] The following detailed embodiments are only used to further illustrate this application and should not be construed as limiting the scope of protection of this application. Those skilled in the art can make some non-essential improvements and adjustments to this application based on the above application content.

[0037] The following is information on domestic suppliers of key related equipment and materials:

[0038] The petroleum coke residue was purchased from China Petroleum & Chemical Corporation (Sinopec).

[0039] The ordinary silicate cement was purchased from Anhui Conch Cement Co., Ltd.

[0040] The quicklime was purchased from Ningxia Jiafeng Chemical Co., Ltd.

[0041] The aluminum powder paste was purchased from Hunan Jinjian New Material Technology Co., Ltd.

[0042] The dihydrate gypsum was purchased from Hubei Longyuan Gypsum Co., Ltd.

[0043] The monomethoxy polyethylene glycol was purchased from Jiangsu Chenguang New Materials Co., Ltd.

[0044] The lactide was purchased from Zhejiang Hisun Biomaterials Co., Ltd.

[0045] The stannous octoate was purchased from Beijing Huawirui Chemical Co., Ltd.

[0046] The ethylenediamine was purchased from China Petrochemical Corporation Nanjing Chemical Industry Co., Ltd.

[0047] The dimethyl sulfoxide was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0048] The 2-(methacryloyloxy)ethyl isocyanate was purchased from Wuhan Changheng Biomedical Technology Co., Ltd.

[0049] The 4-hydroxypyridine was purchased from Suzhou Nop Biotechnology Co., Ltd.

[0050] The tetrahydrofuran was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0051] The dibutyltin dilaurate was purchased from Tianjin Concord Technology Co., Ltd.

[0052] The soapberry powder foam stabilizer was purchased from Henan Chenyuan Biotechnology Co., Ltd.

[0053] The 3-(methacryloyloxy)propyltriethoxysilane was purchased from Jingzhou Jianghan Fine Chemical Co., Ltd.

[0054] The ethanol was purchased from Jiangsu Hanguang Industrial Co., Ltd.

[0055] The 2,2'-azobis(2-methylpropylimidazolium) dihydrochloride was purchased from Suzhou Aodexin Technology Co., Ltd.

[0056] Example 1

[0057] In the preparation of the biomineralized block copolymer, 100g of monomethoxy polyethylene glycol and 50g of lactide were accurately weighed and placed in a reactor. 0.5g of stannous octoate was added as a catalyst. After the system was evacuated, the temperature was raised to 111℃ and maintained for 26 hours to carry out the ring-opening polymerization reaction, obtaining the crude product of mPEG-b-PLA block copolymer. The crude product was dissolved in an appropriate amount of tetrahydrofuran, and methanol was slowly added for precipitation purification. After repeating the process three times, the white solid was collected and dried in a vacuum drying oven at 50℃ for 12 hours to obtain the purified block copolymer. The purified product was then dissolved in 200g of dimethyl sulfoxide with 30g of ethylenediamine and reacted in a constant temperature oil bath at 41℃ for 49 hours. After the reaction, the mixture was transferred to a dialysis bag and dialyzed with deionized water for 72 hours, with the dialysate being replaced every 8 hours. Finally, the mixture was treated with a freeze dryer for 24 hours to obtain the final biomineralized block copolymer. In the preparation of the supramolecular interface integrator, 50g of 2-methacryloyloxyethyl isocyanate and 35g of 4-hydroxypyridine were first dissolved in 250g of anhydrous tetrahydrofuran, and 0.8g of dibutyltin dilaurate catalyst was added. The mixture was refluxed in an oil bath at 63℃ for 13 hours. The reaction progress was monitored by thin-layer chromatography. After the reaction was completed, the solvent was removed by rotary evaporation to obtain a methacrylate monomer containing a pyridine group. 50g of this monomer and 30g of 3-methacryloyloxypropyltriethoxysilane were dissolved together in a mixed solvent composed of 120g of ethanol and 30g of deionized water. 0.5g of 2,2'-azobis(2-methylpropylimidazolium) hydrochloride was added as an initiator. After purging with nitrogen to remove oxygen, the mixture was reacted in an oil bath at 72℃ for 13 hours. During the reaction, mechanical stirring was maintained at a speed controlled at 300rpm. After the reaction was completed, the solvent was removed by rotary evaporation and the mixture was dried in a vacuum drying oven at 60℃ for 24 hours to obtain the finished supramolecular interface integrator.In the preparation of aerated concrete blocks containing petroleum coke residue, 700g of petroleum coke residue is first coarsely crushed to a particle size of less than 5mm using a jaw crusher, and then ground in a QM-1800 ball mill for 2 hours. The resulting powder is then passed through a 200-mesh sieve. The powder, along with 10g of supramolecular interface integrator and 8g of biomineralized block copolymer, is added to a high-speed shear mixer and dry-mixed at 2100rpm for 18 minutes to complete the modification treatment. Separately, 160g of ordinary silicate cement, 100g of quicklime, and 35g of dihydrate gypsum are added to a JQ-500 forced mixing pot and pre-mixed at 100rpm for 3 minutes. Then, the modified petroleum coke residue is added to the mixing pot and dry-mixed at 150rpm for 4 minutes. Add an appropriate amount of water and increase the speed to 300 rpm, stirring at high speed for 5 minutes to form a uniform slurry; pre-mix and disperse 0.9g of aluminum powder paste with 40℃ warm water and 0.5g of soapberry powder foam stabilizer, then add it to the slurry and stir at 350 rpm for 30 seconds, then immediately pour it into a 600mm×600mm×200mm mold; let it stand in a 55℃ curing chamber for 3 hours to generate gas, and after pre-curing for 2 hours, demold it and mechanically cut it using an automatic cutting machine; finally, send the blank into an autoclave, heat it to 183℃ at a rate of 30℃ / h, and cure it under constant pressure at 1.1MPa saturated steam pressure for 13 hours, then depressurize and cool it at a rate of 0.2MPa / h, and allow it to cool naturally for 24 hours after exiting the furnace to obtain the finished aerated concrete block.

[0058] Example 2

[0059] The specific implementation method is the same as in Example 1, except that the preparation of the biomineralized block copolymer is as follows: 100g of monomethoxy polyethylene glycol and 45g of lactide are reacted under vacuum at 110°C for 24h in the presence of 0.4g of stannous octoate catalyst to obtain mPEG-b-PLA block copolymer, which is purified by methanol precipitation and then vacuum dried; then the above copolymer is reacted with 28g of ethylenediamine in 220g of dimethyl sulfoxide solution at 40°C for 48h; finally, the product is dialyzed and freeze-dried to obtain the biomineralized block copolymer. Preparation of supramolecular interface integrator: 48g of 2-methacryloyloxyethyl isocyanate and 32g of 4-hydroxypyridine were added to 230g of anhydrous tetrahydrofuran and reacted at 60℃ for 12h under the catalysis of 0.7g of dibutyltin dilaurate to obtain a methacrylate monomer containing a pyridine group; 45g of the methacrylate monomer containing a pyridine group and 28g of 3-methacryloyloxypropyltriethoxysilane were dissolved in a mixed solvent composed of 110g of ethanol and 28g of water, and 0.4g of 2,2'-azobis(2-methylpropylimidazolium) hydrochloride were added. The mixture was reacted at 70℃ for 12h under nitrogen protection. After the reaction was completed, the mixture was dried under vacuum to obtain the supramolecular interface integrator. Preparation of aerated concrete blocks containing petroleum coke residue: 650g of petroleum coke residue was coarsely crushed by a jaw crusher and then ground in a ball mill; the petroleum coke residue powder, 12g of supramolecular interface integrator, and 6g of biomineralized block copolymer were added to a high-speed shear mixer and dry-mixed at 2000rpm for 20min; 180g of ordinary silicate cement, 90g of quicklime, and 40g of dihydrate gypsum were added to a forced mixing pot and premixed for 4min; then the modified petroleum coke residue was added to the mixing pot and dry-mixed for 5 minutes. min; add an appropriate amount of water and stir at high speed to form a uniform slurry; mix and disperse 0.8g of aluminum powder paste with 39℃ water and 0.4g of soapberry powder foam stabilizer, add it to the slurry, stir at high speed and immediately pour it into the mold; let it stand in the curing chamber at 54℃ to generate gas and pre-cur, then demold and mechanically cut; finally, send the green body into the autoclave, heat it to 182℃, and cure it under constant pressure at 1.0MPa saturated steam pressure for 12h, then reduce the pressure and temperature, and let it cool naturally after being taken out of the furnace to obtain the aerated concrete block product.

[0060] Example 3

[0061] The specific implementation method is the same as in Example 1, except that the preparation of the biomineralized block copolymer is as follows: 100g of monomethoxy polyethylene glycol and 55g of lactide are reacted under vacuum at 112°C for 28h in the presence of 0.6g of stannous octoate catalyst to obtain mPEG-b-PLA block copolymer, which is purified by methanol precipitation and then vacuum dried; then the above copolymer is reacted with 32g of ethylenediamine in 250g of dimethyl sulfoxide solution at 42°C for 50h; finally, the product is dialyzed and freeze-dried to obtain the biomineralized block copolymer. Preparation of supramolecular interface integrator: 52g of 2-methacryloyloxyethyl isocyanate and 38g of 4-hydroxypyridine were added to 270g of anhydrous tetrahydrofuran and reacted at 65℃ for 14h under the catalysis of 0.9g of dibutyltin dilaurate to obtain a methacrylate monomer containing a pyridine group; 55g of the methacrylate monomer containing a pyridine group and 32g of 3-methacryloyloxypropyltriethoxysilane were dissolved in a mixed solvent composed of 130g of ethanol and 32g of water, and 0.6g of 2,2'-azobis(2-methylpropylimidazolium) hydrochloride were added. The mixture was reacted at 74℃ for 14h under nitrogen protection. After the reaction was completed, the mixture was dried under vacuum to obtain the supramolecular interface integrator. Preparation of aerated concrete blocks containing petroleum coke residue: 720g of petroleum coke residue was coarsely crushed by a jaw crusher and then ground in a ball mill; the petroleum coke residue powder, 16g of supramolecular interface integrator, and 10g of biomineralized block copolymer were added to a high-speed shear mixer and dry-mixed at 2200rpm for 16min; 120g of ordinary Portland cement, 110g of quicklime, and 45g of dihydrate gypsum were added to a forced mixing pot and premixed for 2min; then the modified petroleum coke residue was added to the mixing pot and dry-mixed. 3 min; add appropriate amount of water and stir at high speed to form a uniform slurry; mix and disperse 1.0g aluminum powder paste with 41℃ water and 0.6g soap pod powder foam stabilizer, add to the slurry, stir at high speed and immediately pour into the mold; let stand in the curing chamber at 56℃ for gas generation and pre-curing, then demold and mechanically cut; finally send the green body into the autoclave, heat to 184℃, and cure under constant pressure at 1.2MPa saturated steam pressure for 14h, then reduce pressure and temperature, and let it cool naturally after being taken out of the furnace to obtain the aerated concrete block product.

[0062] Comparative Example 1

[0063] The specific implementation method is the same as in Example 1, except that no biomineralized block copolymer is added when preparing the aerated block.

[0064] Comparative Example 2

[0065] The specific implementation method is the same as in Example 1, except that no supramolecular interface integrator is added when preparing the aerated block.

[0066] Comparative Example 3

[0067] The specific implementation method is the same as in Example 1, except that no biomineralized block copolymer and supramolecular interface integrator are added when preparing the aerated block.

[0068] Performance testing

[0069] Performance testing methods were conducted according to the national standard GB / T 11968-2020 "Autoclaved Aerated Concrete Blocks". For the dry density test, the samples were placed in a 105±5℃ forced-air drying oven to constant weight. After cooling to room temperature, the sample dimensions were measured using a vernier caliper with an accuracy of 0.1mm, and the volume was calculated. The mass was weighed using an electronic balance with an accuracy of 0.1g. The dry density was calculated as the ratio of mass to volume, and the arithmetic mean of three samples was taken. For the compressive strength test, a WAW-1000 microcomputer-controlled electro-hydraulic servo universal testing machine was used. The samples were processed into 100mm×100mm×100mm cube specimens and uniformly loaded at a loading rate of 2.0kN / s until specimen failure. The maximum load value was recorded, and the compressive strength was calculated. Five specimens were ultimately selected. The arithmetic mean of the specimens was used for the drying shrinkage test. A vertical shrinkage tester was used. The specimens were processed into prisms of 40mm × 40mm × 160mm, dried to constant weight in a drying oven at 50±2℃, and then placed in a constant temperature and humidity chamber at 20±2℃ and 43%±2% relative humidity. The length change was measured using a dial indicator at 3d, 7d, 14d, and 28d. The final value was calculated according to the drying shrinkage formula, and the arithmetic mean of the three specimens was taken. The thermal conductivity test was conducted using a DRPL-III type flat plate thermal conductivity meter. The specimens were processed into 300mm × 300mm × 30mm specimens and tested at an average temperature of 25℃. The arithmetic mean of the test results of two specimens was taken as the final result.

[0070] Performance test results:

[0071] Table 1: Performance test results of each embodiment and comparative example

[0072]

[0073] As shown in Table 1, Examples 1-3 effectively solved the technical problems of low utilization rate of petroleum coke residue and poor interfacial bonding leading to insufficient product strength in aerated concrete blocks by adding biomineralized block copolymers and supramolecular interface integrators. Specifically, the dry density of Examples 1-3 was maintained at 598-635 kg / m³. 3The material exhibits a relatively low level of strength, while maintaining a high compressive strength range of 5.5-6.1 MPa. This indicates that the two modifiers work synergistically, ensuring both the material's lightweight nature and significantly enhancing its mechanical properties. In contrast, Comparative Example 1, lacking the biomineralized block copolymer, has a compressive strength reduced to 4.2 MPa; Comparative Example 2, lacking the supramolecular interface integrator, has a compressive strength of 4.5 MPa; and Comparative Example 3, lacking both modifiers, has the lowest compressive strength at only 3.6 MPa, with the highest dry density reaching 658 kg / m³. 3 This fully demonstrates that the lack of modifiers leads to weak bonding between petroleum coke residue and the matrix, resulting in increased material density but significantly reduced strength.

[0074] Furthermore, the drying shrinkage values ​​of Examples 1-3 were controlled in a lower range of 0.39-0.43 mm / m, while those of Comparative Examples 1-3 reached 0.58, 0.52, and 0.72 mm / m, respectively, indicating that the modifier significantly improved the volume stability of the product by improving the interfacial structure and inhibiting shrinkage cracks. Regarding thermal conductivity, Examples 1-3 had a conductivity of 0.128-0.136 W / (m·K), lower than the 0.139-0.152 W / (m·K) of Comparative Examples 1-3, demonstrating that the modifier promoted the homogenization of the pore structure and enhanced the thermal insulation performance. In summary, the biomineralized block copolymer forms a robust interfacial layer by inducing a mineralization reaction on the surface of petroleum coke residue, while the supramolecular interfacial integrator achieves effective bridging of the organic-inorganic phases through intermolecular forces. The synergistic effect of both significantly improves the utilization rate and interfacial bonding strength of petroleum coke residue, enabling the aerated concrete block to simultaneously possess excellent mechanical properties, dimensional stability, and thermal performance.

[0075] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the protection scope of the present invention.

Claims

1. An air entrained block comprising petroleum coke, characterised in that, The raw materials include the following weight parts: Petroleum coke residue: 600-750 parts by weight; Ordinary Portland cement: 120-200 parts by weight; Quicklime: 80-120 parts by weight; Aluminum powder paste: 0.6-1.2 parts by weight; Dihydrated gypsum: 20-50 parts by weight; Biomineralization block copolymer: 4-12 parts by weight; Supramolecular interface integration agent: 8-20 parts by weight; The preparation method of the biomineralization block copolymer comprises: A1, reacting monomethoxy polyethylene glycol and lactide under the catalysis of stannous octoate at 110-112℃ under vacuum conditions to obtain mPEG-b-PLA block copolymer, which is purified by methanol precipitation and then vacuum dried; A2, then reacting mPEG-b-PLA with ethylenediamine in a dimethyl sulfoxide solution at 40-42℃; finally, the product is dialyzed and freeze-dried.

2. The petroleum coke containing aerated block according to claim 1, characterized in that, In step A1, the reaction time under vacuum at 110-112℃ is 24-30h.

3. The petroleum coke containing aerated block according to claim 1, characterized in that, In step A2, the reaction time in the dimethyl sulfoxide solution at 40-42℃ is 48-50h.

4. The petroleum coke containing aerated block according to claim 1, characterized in that, The preparation method of the supramolecular interface integration agent comprises: B1, adding 2-(methacryloyloxy)ethyl isocyanate and 4-hydroxypyridine into anhydrous tetrahydrofuran, reacting at 60-65℃ under the catalysis of dibutyltin dilaurate to obtain a methacrylate monomer containing a pyridine group; B2, dissolving the methacrylate monomer containing a pyridine group and 3-(methacryloyloxy)propyl triethoxysilane in a mixed solvent of ethanol and water, adding 2,2'-azobis(2-methylpropylimid) dihydrochloride, reacting at 70-74℃ under nitrogen protection, and vacuum drying after the reaction is completed.

5. The petroleum coke containing aerated block according to claim 4, characterized in that, In step B1, the reaction time at 60-65℃ is 12-14h.

6. The petroleum coke containing aerated block according to claim 4, characterized in that, In step B2, the reaction time at 70-74℃ is 12-14h.

7. A process for the production of an air entrained block containing petroleum coke residues according to any one of claims 1 to 6 characterised by the steps of It comprises: S1, the petroleum coke residue is coarsely crushed by a jaw crusher and then ground in a ball mill; The petroleum coke residue powder, the supramolecular interface integration agent and the biomineralization block copolymer are added into a high-speed shearing mixer for dry mixing; S2, the ordinary Portland cement, the quicklime and the dihydrated gypsum are added into a forced stirring pot for premixing; then the modified petroleum coke residue is added into the stirring pot for dry mixing; water is added, and high-speed stirring is performed to form a uniform slurry; the aluminum powder paste is mixed and dispersed with 38-42℃ water and soap pod powder foam stabilizer, and then added into the slurry, which is immediately poured into a mold after high-speed stirring; the mold is placed in a 53-57℃ curing room for standing, gas releasing, pre-curing, demolding and mechanical cutting; S3, finally, the green body is sent into a steam autoclave, heated to 182-184℃, and cured under constant pressure at a saturated steam pressure of 1.0-1.2MPa, and then depressurized and cooled, and naturally cooled after being taken out of the furnace.

8. The preparation method according to claim 7, characterized in that, In step S1, the dry mixing speed is 2000-2200rpm, and the dry mixing time is 15-20min.

9. The preparation method according to claim 7, characterized in that, In step S2, the premixing time is 2-4min, and the dry mixing time is 3-5min.

10. The method of claim 7, wherein, In step S3, the constant pressure curing time is 12-14h.